Large Print Stories From the Bible (India : Om books international, 2019)
"Make reading time a delightful learning experience, introducing children to the stories and characters of the Bible with this vibrant, illustrated book, where God brings to life day and night, Adam and Eve and all of creation. Read all about Noah and his ark full of animals, about clever David and the giant, Goliath, the wise Moses and the ten commandments and many more interesting stories.".
The story of creation, Adam and Eve, Cain and abel, The story of Noah, The Story of Moses.
Large Print Stories From the Bible
Keywords: Stories from the Bible